PLANE OF KNOWLEDGE IN THE SPACE OF EDUCATOR’S COMPETENCE - Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 2009)
Spread of constructive teaching/learning theory results in a bigger research interest in knowledge and its acquisition, which is directly related with competence development. The focus is laid on the concept of knowledge, their links with sense and intertwining of knowledge and values (and especially moral ones). The research results revealed that educators’ attitude to deepening of knowledge is based on the level of knowledge acquisition. The priority is laid on teaching to learn, development of thinking, spread of spiritual powers, new technologies of education, underlying ideas of general education programmes and standards and about 65.3–50.9 percent of teachers refer to them as very important. Whereas the least attention is paid to education management, understanding of feelings, imagination and partially to perception of volitional development, diagnostics and evaluation of progress and achievement and education planning. The statistical data analysis shows that all the identified knowledge priorities, with the exception of teaching to learn, have very weak links with spiritual values or such links are absent (with knowledge of education management, memory development, methods of pedagogical interaction, peculiarities of education and upbringing, new education technologies). Spiritual values are linked with knowledge of feelings, volition, imagination and partially with education planning. It was established that gender, qualification, working experience and workplace have insignificant effect on teachers’ attitude and only on knowledge related with external elements of educational process (general programmes, education management, planning, teaching to learn).